Non-invasive Cardiac Output Monitoring in Neonates - O'Neill, Roisin; Dempsey, Eugene M.; Garvey, Aisling A.; Schwarz, Christoph E. (Frontiers in Pediatrics, 2021)
Circulatory monitoring is currently limited to heart rate and blood pressure assessment in the majority of neonatal units globally. Non-invasive cardiac output monitoring (NiCO) in term and preterm neonates is increasing, where it has the potential to enhance our understanding and management of overall circulatory status. In this narrative review, we summarized 33 studies including almost 2000 term and preterm neonates. The majority of studies evaluated interchangeability with echocardiography. Studies were performed in various clinical settings including the delivery room, patent ductus arteriosus assessment, patient positioning, red blood cell transfusion, and therapeutic hypothermia for hypoxic ischemic encephalopathy. This review presents an overview of NiCO in neonatal care, focusing on technical and practical aspects as well as current available evidence. We discuss potential goals for future research. Funding: This Review was supported by Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) Project number 420536451 and National Children’s Research Centre, Ireland (D/18/6).